ALTERNATIVAS PARA IMPLANTAÇÃO DE UM SISTEMA TÉRMICO DE HIGIENIZAÇÃO E SECAGEM DO LODO GERADO EM ESTAÇÃO DE TRATAMENTO ANAERÓBIO DE ESGOTO SANITÁRIO DE PEQUENO PORTE - Kuk, Tiago Neumann (2019)
The sludge resulting from sanitary sewage treatment has nutrients and organic matter, making it a usable by-product in agriculture. For this to be possible, it is necessary to dewater this sludge, which, in the natural state and from anaerobic reactors, has around 95% of water and mainly, it is necessary a process of hygienization for inactivation of the present microorganisms, in order to be considered sanitary safe. With the expectation that the rates of collection and treatment of sewage will increase in Brazil and with the requirements of more efficiency in the treatment, volumes of sludge generated will be increased and for small Wastwater Treatment Plants – WWTPs (up to 30.000 inhabitants), besides the process by means of chemical products, searching for other forms of hygienization. This research investigated a small WWTP in which methane results present in biogas generated in reactor were (69,45 ± 3,74)%. The sludge of this reactor was tested in 3 campaigns using prototypes tanks with radiant floors, heated by solar energy and electric energy that simulated methane demand. In the first campaign, in metallic tank, at the most unfavorable points of the 20cm layer of sludge in the natural state with 5,11% of total solids, the average temperature was 44,6ºC and the maximum of 48,6ºC, not reaching the levels of recommended temperature and cleaning time (70ºC for 30 minutes or 54ºC for 2 hours). In the second campaign, also in metallic tank, the most unfavorable points of the layer of 10cm of dewatered sludge in a drying bed, with 39,56% of total solids, reached average of 54,7ºC and maximum of 55,4ºC, being considered sanitized after 25 hours, responding an unknown information that remained on the behavior of the sludge sanitized by thermal path in this total solids level. In the third campaign in metallic tank, in the unfavorable points of 10cm of layer of sludge in the natural state with 4,41% of total solids, an average of 55,6ºC and maximum of 57,1ºC was reached, whereas the time of hygiene was 11,43 hours. However, this same sludge in a 10cm layer in tank with concrete floor, did not reach temperatures to be considered sanitized, thus the most unfavorable part reached average of 49,7ºC and maximum of 53,8ºC. Drying of the sludge was satisfactory in all the campaigns, reaching final total solids of 76,44%, 70,86% and 77,02%, respectively. The comparison of these tests and other researches, resulted that the most favorable alternative for the WWTP studied is a system that performs the sanitation and drying of the sludge on the 40% of total solids level by means of 2 metallic tanks with 50m² of radiant floor, each one, working 3 cycles monthly, using an initial solar heating system and a complement of 9.691,88Nm³/month of methane. The system will be self-sufficient, because for this WWTP, the calculated methane is 11.640Nm³/month, but due to oscillation in the biogas production it is necessary to store it in a gasometer of 80m³.